1998
DOI: 10.1021/ed075p578
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Science: Network-Deliverable Curricula

Abstract: The Molecular Science systemic reform project, which has just begun its third year, is developing network-deliverable curricula for the first two years of Chemistry. 1 The goals of the project are to prepare students who have a deep understanding of chemistry concepts and principles, have learned collaboration skills, can use the modern-technology tools of the chemist, and can write about chemistry. In addition, the project is integrating technology and telecommunications into the instructional process and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…In this stage, they read and assess portfolios created by other groups, assigning scores and providing justification. Peer assessment has long been used in writing courses as well as in a variety of other fields (Bonwell & Eison, 1991;Freeman, 1995;Rafiq & Fullerton, 1996;Russell, Chapman & Wegner, 1998). This research has shown that peer evaluation supports collaborative group work in general and, in particular, it supports a shift in students' perspective from writing for the teacher to writing for their peers and, ultimately, for a larger audience.…”
Section: Taxonomy Of Ciitn Learning Activitiesmentioning
confidence: 99%
“…In this stage, they read and assess portfolios created by other groups, assigning scores and providing justification. Peer assessment has long been used in writing courses as well as in a variety of other fields (Bonwell & Eison, 1991;Freeman, 1995;Rafiq & Fullerton, 1996;Russell, Chapman & Wegner, 1998). This research has shown that peer evaluation supports collaborative group work in general and, in particular, it supports a shift in students' perspective from writing for the teacher to writing for their peers and, ultimately, for a larger audience.…”
Section: Taxonomy Of Ciitn Learning Activitiesmentioning
confidence: 99%
“…Although I would like to believe that using WebCT enhanced student learning, I cannot demonstrate this. To my knowledge, only one web-based writing tool, Calibrated Peer Review (Russell et al, 1998) has been shown to consistently improve student learning in various disciplines in a measurable way. It is instead likely that students who are interested in the subject matter, and who would earn good grades with or without an Internet component, are also the ones who made most use of WebCT and read and wrote most of the "Discussion postings".…”
Section: Course Notes 77mentioning
confidence: 96%
“…Apparently what worked best in his case was to require discussion of a question each week, something that would unfortunately be quite impractical in a class of several hundred students. Calibrated Peer Review™ (Russell et al, 1998) is a fully automated system to grade written assignments, but its scope and extent goes well beyond the simple online discussion provided by WebCT and requires intensive preparation and planning.…”
Section: Webct's Disadvantagesmentioning
confidence: 99%
“…While we were concerned with plagiarism, the PeerMark feature of the program also allowed for online peer evaluation, similar to that of Calibrated Peer Review (CPR), an online program which allows for electronic submission and review of student work (16)(17)(18). Teaching assistants graded all writing assignments using the GradeMark component of Turnitin.…”
Section: Motivation For Changementioning
confidence: 99%